A Courageous, Creative, Though Cautionary, Tale: Commentary on Dr. Lauren Levine's Paper, "A Mutual Survival of Destructiveness and Its Creative Potential for Agency and Desire". Issue 1 (2nd January 2016) - Glennon, Stefanie Solow
Abstract : This discussion lauds the richness and in-depth nature of Lauren Levine's clinical work, including the efficacy of a much needed consultation with a colleague. The analytic work is viewed in light of concerns raised by senior relational analysts in a previous issue of Psychoanalytic Dialogues . Additional thoughts stimulated by the presentation are offered by the discussant.